Pengaruh Praktik Berbagi Pengetahuan terhadap Kepuasan Kerja: Peran Mediasi Komitmen Belajar dan Adaptabilitas Pribadi - Bimmo Dwi Baskoro (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2020)
The purpose of this study is to discuss and analyze the relationships knowledge-sharing on job satisfaction mediated by adaptability interpersonal and learning commitment. The subjects of this study were all employees in the telecommunications company (PT. BBT) with 116 employees. This research uses causal associative analysis using a quantitative approach. The sampling technique used is saturated samples. Data were collected using a questionnaire that had been tested by SEM-PLS. The results showed that the practice of sharing knowledge, adaptability interpersonal, and learning commitment affect job satisfaction; learning commitment mediates knowledge-sharing practices on job satisfaction. The method of sharing knowledge on job satisfaction is not mediated by adaptability interpersonal.